Epidemiology and aetiology of maternal bacterial and viral infections in low- and middle-income countries - Velu, Prasad Palani; Gravett, Courtney A; Roberts, Tom K; Wagner, Thor A; Zhang, Jian Shayne F; Rubens, Craig E; Gravett, Michael G; Campbell, Harry; Rudan, Igor (Journal of global health, 2011)
Maternal morbidity and mortality in low- and middle-income countries has remained exceedingly high. However, information on bacterial and viral maternal infections, which are important contributors to poor pregnancy outcomes, is sparse and poorly characterised. This review aims to describe the epidemiology and aetiology of bacterial and viral maternal infections in low- and middle-income countries. A systematic search of published literature was conducted and data on aetiology and epidemiology of maternal infections was extracted from relevant studies for analysis. Searches were conducted in parallel by two reviewers (using OVID) in the following databases: Medline (1950 to 2010), EMBASE (1980 to 2010) and Global Health (1973 to 2010). Data from 158 relevant studies was used to characterise the epidemiology of the 10 most extensively reported maternal infections with the following median prevalence rates: Treponema pallidum (2.6%), Neisseria gonorrhoeae (1.5%), Chlamydia trachomatis (5.8%), Group B Streptococcus (8.6%), bacterial vaginosis (20.9%), hepatitis B virus (4.3%), hepatitis C virus (1.4%), Cytomegalovirus (95.7% past infection), Rubella (8.9% susceptible) and Herpes simplex (20.7%). Large variations in the prevalence of these infections between countries and regions were noted. This review confirms the suspected high prevalence of maternal bacterial and viral infections and identifies particular diseases and regions requiring urgent attention in public health policy planning, setting research priorities and donor funding towards reducing maternal morbidity and mortality in low- and middle-income countries.